2001
DOI: 10.1002/jlcr.482
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of no‐carrier‐added [124I]A14‐iodoinsulin as a radiotracer for positron emission tomography

Abstract: A14‐Iodoinsulin is a close biochemical and pharmacological mimic of insulin. Human insulin was labelled in its A chain tyrosine‐14 residue by direct iodination with the positron‐emitter iodine‐124 (β+=25.6%; t1/2=4.15 days) to provide a radiotracer for imaging with positron emission tomography (PET). Several reagents were compared for conversion of cyclotron‐produced [124I]iodide into a reactive species for the labelling reaction. Radiochemical yields from the use of Iodo‐Gen®, Chloramine‐T, N‐bromosuccinimide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Numerous studies were conducted since the first report by Kondo et al in 1977 [ 70 ]. The results from these studies suggested that 124 I can be successfully produced for research and clinical use by using low-energy cyclotrons that are available routinely for production of 11 C and 18 F-labeled imaging pharmaceuticals for standard care [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ]. Consequently, the 124 Te(p,n) 124 I production process is being used extensively in the research and clinical environments worldwide.…”
Section: Overview Of 124 I Production Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies were conducted since the first report by Kondo et al in 1977 [ 70 ]. The results from these studies suggested that 124 I can be successfully produced for research and clinical use by using low-energy cyclotrons that are available routinely for production of 11 C and 18 F-labeled imaging pharmaceuticals for standard care [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ]. Consequently, the 124 Te(p,n) 124 I production process is being used extensively in the research and clinical environments worldwide.…”
Section: Overview Of 124 I Production Processesmentioning
confidence: 99%
“…Additionally, tellurium tends to blow up upon heating. The tellurium target for proton irradiation has been prepared by the three different methods: (1) filling 124 Te in an aluminum capsule under He atmosphere [ 70 , 84 ], (2) introducing melted enriched tellurium onto a support plate [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 86 ], and (3) electroplating tellurium on a nickel-coated copper substrate [ 45 , 48 , 97 , 98 ].…”
Section: Overview Of 124 I Production Processesmentioning
confidence: 99%
“…A minimum contamination can be seen starting around 10 MeV, peaking around 13 MeV and decreases with increasing energy. So, it is clear that the elimination of radionuclidic impurities is not always possible even with a wide energy selection and high enrichment as stated by Glaser et al, (2001), Sheh et al, (2000 and Michael et al, (1981). The production of 123 I were found appropriate for small, medium-sized cyclotrons and is convenient for economical and availability purposes.…”
Section: Fig 5 Reaction Cross Sections Of Producing 124 I Frommentioning
confidence: 99%
“…The use of 124 I radioisotope has extended in medicine recently due to its diagnostic and therapeutic potential. Since its half life is 4.2 days and it has 23% positron decay (IAEA, 2009); it is possible to use 124 I for positron emission tomography (PET) radiopharmaceuticals (Glaser et al, 2001;Sheh et al, 2000;Michael et al, 1981). 124 I isotope were formerly considered as an impurity in 123 I production, since it has diagnostic and therapeutic potential the production of 124 I is becoming more widespread (Herzog et al, 2002;Pentlow et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, insulin has been labeled with 124 I on the fourteenth amino acid residue (tyrosine) using electrophilic radiolabeling conditions [119]. The nucleoside analog 2′-fluoro-2′-deoxy-1β-D-arabinofuranosyl-5-iodouracil (FIAU) has also been labeled using Na[…”
Section: Radiobromine and Radioiodine For Petmentioning
confidence: 99%